Dexmedetomidine vs. Other Sedatives in Mechanically Ventilated Sepsis Patients: Updated Meta-analysis - Rizky Eka Putera; Rafael Bagus Yudhistira; Livilia Abigail Onggowasito; Nathania Ella Sudiono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Introduction. Globally, the incidence of sepsis is estimated at over 400 cases per 100,000 population annually, making it a major public health concern. . In this setting, sedation is essential to ensure patient-ventilator synchrony and reduce physiological stress. Dexmedetomidine is a selective α₂-agonist often used instead of traditional sedatives because it provides light sedation, lowers the risk of delirium, and may reduce inflammation. However, clinical outcomes remain inconsistent across studies. To assess the clinical effects of dexmedetomidine compared to other sedatives in mechanically ventilated sepsis patients.Methods. A comprehensive literature search of Pubmed, Scopus, Cochrane Central, Scilit, and Epistemonikos was performed to identify studies published from 2020 to 2025. Inclusion criteria included Randomized Controlled Trial (RCT) studies that directly compared dexamethomidine as sedation and involving sepsis patients with mechanical ventilation. Risk of Bias was estimated using RoB2.0 and meta analysis was using Revman 5.4.Results. Eight randomized control trials (n = 1119) were included. Compared to other sedatives, dexmedetomidine prolonged hospital LOS significantly (MD = 1.47; 95% CI: 0.59 to 2.34; p = 0.001), reduced ICU LOS significantly (MD = -0.91; 95%CI = -1.51 to -0.29; p = 0.004), not improving the event of mortality insignificantly (OR = 0.99; 95% CI: 0.71–1.37; p = 0.95), reduced ventilator-free days insignificantly (MD = –0.85; 95% CI = –1.94 to 0.25; p = 0.13), and improved lactate clearance insignificantly (MD = 0.54; 95%CI = -0.41 to 1.49; p = 0.21)Conclusion. Dexmedetomidine reduces ICU length of stay and may offer early mortality benefits at 28 days in mechanically ventilated sepsis patients. However, its effects on hospital stay, lactate clearance, and ventilator-free days remain uncertain, and further standardized trials are needed.